2020
DOI: 10.1371/journal.pone.0218228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate and high intensity isocaloric aerobic training upon microvascular reactivity and myocardial oxidative stress in rats

Abstract: Systemic and central cardiovascular adaptations may vary in response to chronic exercise performed with different intensities and volumes. This study compared the effects of aerobic training with different intensities but equivalent volume upon microvascular reactivity in cremaster muscle and myocardial biomarkers of oxidative stress in Wistar rats. After peak oxygen uptake (VO 2peak) assessment, rats (n = 24) were assigned into three groups: moderateintensity exercise training (MI); high-intensity exercise tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Gomes et al [ 42 ] have also shown that aerobic exercise is more superior in combating oxidative stress than resistance-type exercise. Further, some studies observed that well-trained exercise condition can even overcome high-intensity-induced oxidative damage in both aerobic and resistance exercise [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gomes et al [ 42 ] have also shown that aerobic exercise is more superior in combating oxidative stress than resistance-type exercise. Further, some studies observed that well-trained exercise condition can even overcome high-intensity-induced oxidative damage in both aerobic and resistance exercise [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three months of aerobic exercise is found to reduce GRP-78, IRE1, and p-eIF2 α mRNA and protein levels in subcutaneous fat tissue and blood mononuclear cells of obese adults [ 48 ]. Treadmill exercise training can reduce GRP-78, p-PERK, p-eIF2 α , ATF-6, XBP1, CHOP, and cleaved-caspase-3 expression to improve the cardiovascular function and reduce myocardial infarction in rats [ 49 ]. Correspondingly, 3 weeks of high-intensity treadmill exercise can strengthen the ER stress degree in the brain tissue of obese mice fed with a HFD, with the hypothalamus presenting the highest ER stress degree [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the research investigated the effect of isocaloric aerobic exercise with medium and high intensity on capillary reaction and heart muscle oxidative stress in rats. The results showed that higher exercise intensity caused more improvement in myocardial antioxidant defense, while the increase in capillary reactivity seems to depend more on exercise volume than exercise intensity (30).…”
Section: Resultsmentioning
confidence: 89%